Metode Komunikasi Dakwah Rasulullah (Kajian Tematik dalam Kitab á¹¢aá¸¥Ä«á¸¥ Muslim) - Ridwan, Ridwan; Sari, Hijrayanti (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2021)
This research aims to find out the methods of da'wah and communication of the Prophet (peace be upon him) in the book of á¹¢aá¸¥iá¸¥ Muslim. The research method used is a qualitative library study with historical, normative and sociological approaches. The results of this study show that the methods of da'wah communication used by the Prophet include: methods of correspondence, patience, tenderness, methods of denial of imperisibility, priority scale, ease, bringing good news, methods of clarification, and praying. The methods of da'wah used by the Prophet are quite diverse so that these methods can be used in accordance with the conditions of mad'u faced by the dais. All elements of communication are carried out by the Prophet very precisely. The quality of the communicator can be seen in his integrity which has a nature of patience and a soft heart.